3D continuum percolation approach and its application to lava-like fuel-containing materials behaviour forecast - Zhydkov, V.O. (Condensed Matter Physics, 2009)
The paper is devoted to the theoretical study of elementary permeable objects percolation and its application
to real physical objects. Spheres and isotropic oriented capped sticks were chosen as elementary geometrical
objects for percolation simulation, physically adequate for radiation defects behaviour description in brittle
dielectrics, particularly in the so-called Lava-like Fuel Containing Materials (LFCM), where it effects their
mechanical steadiness. LFCMs is high-radioactive glass, which was formed during active stage of well-known
heavy nuclear accident, that occurred at Chornobyl nuclear facility in 1986. Physical processes taking place in
the materials are of great practical interest. Furthermore, when applying percolation models to LFCM objects,
an approximate behaviour forecast can be created. From the results of simulation, it appears that physical
properties of the LFCM should drastically change within in the period of 2015/2045 calendar years, depending
on variations in nuclear fuel content. Ця робота присвячена теоретичному вивченню перколяцiйних задач на елементарних проникаючих об’єктах та його застосуванню до реальних фiзичних об’єктiв. Сфери та iзотропно орiєнтованi скругленi палички були обранi як елементарнi геометричнi об’єкти для моделювання перколяцiї, фiзично адекватнi для опису поведiнки крихких матерiалiв, що мiстять радiацiйнi дефекти, зокрема до так званих лавоподiбних паливовмiсних матерiалiв (ЛПВМ), де цi дефекти суттєвим чином впливають на механiчну стiйкiсть. ЛПВМ являють собою високорадiоактивне скло, що сформувалося у перебiгу активної фази добре вiдомої важкої ядерної аварiї, що вiдбулася на Чорнобильськiй Атомнiй Електростанцiї у 1986 роцi. Фiзичнi процеси, що мають мiсце у цих матерiалах, становлять великий практичний iнтерес. Застосовуючи перколяцiйнi моделi до ЛПВМ, можливо створити приблизний прогноз їх поведiнки. З результатiв моделювання випливає, що фiзичнi властивостi ЛПВМ корiнним чином змiняться в перiод 2015 2045 року, в залежностi вiд вмiсту палива в них.